Advancements In Hematopoietic Stem Cell Therapy - Bangash, Sudhair Abbas; Baig, Robal Naseem; Khan, Usama Hasan; Nisa, Fizza Tun (Journal of Neonatal Surgery, 2025)
Background: Over the past few years, Hematopoietic Stem Cell Therapy (HSCT) has made remarkable progress in taking diseases away from patients like leukemia, lymphoma, or sickle cell anemia. Even with clinical success, satisfaction remains a major concern for patients treated. Introduction The study aimed to investigate factors related to satisfaction in HSCT and to determine the contribution of demographic, treatment-related, and behavioral variables to satisfaction. Objective: This study mainly aimed to explore the influence of age, gender, education, occupation, product application frequency, and other treatment-related factors on patient satisfaction with HSCT. Methods: This research uses a quantitative descriptive research design, using primary and secondary data. HSCT experiences were assessed among a sample of 200 patients and 150 healthcare professionals surveyed using structured questionnaires. A variety of analyses were conducted on the data, including descriptive statistics, normality tests (Shapiro-Wilk), reliability tests (Cronbach’s Alpha), correlation analysis, and regression modeling to predict significant predictors of patient satisfaction. Results: Results showed a strong negative correlation between Age and Satisfaction, indicating older patients reported a lower satisfaction level. However, the Product Usage Frequency indicated a moderate negative association with satisfaction, implying that the more frequently the treatments were applied, the less satisfied the customers were. Neither gender nor education or occupation was a significant predictor of satisfaction. All tests for normality showed that the data was not normal, thus, we probably would use nonparametric methods. Conclusion: Age and treatment frequency for HSCT in systematically increasing patient satisfaction: This study suggests the need for further investigation of the association between frequency of treatment and its effect on patient satisfaction in HSCT The results indicate that older patients and more frequently treated patients may have lower satisfaction and should be the focus of further investigation in the context of personalized care strategies. Further research could also include additional factors — psychological well-being, long-term outcomes, etc. — that could provide a broader perspective for the improvement of HSCT patients..